1998
DOI: 10.1016/s0092-8674(00)81167-8
|View full text |Cite
|
Sign up to set email alerts
|

Jak2 Is Essential for Signaling through a Variety of Cytokine Receptors

Abstract: A variety of cytokines activate receptor-associated members of the Janus family of protein tyrosine kinases (Jaks). To assess the role of Jak2, we have derived Jak2-deficient mice. The mutation causes an embryonic lethality due to the absence of definitive erythropoiesis. Fetal liver myeloid progenitors, although present based on the expression of lineage specific markers, fail to respond to erythropoietin, thrombopoietin, interleukin-3 (IL-3), or granulocyte/macrophage colony-stimulating factor. In contrast, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

22
665
1
6

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 997 publications
(694 citation statements)
references
References 53 publications
22
665
1
6
Order By: Relevance
“…There is also good evidence suggesting essential role for Jak2-STAT5 pathway in erythropoiesis in vitro and in vivo (Wakao et al, 1997;Iwatsuki et al, 1997;Parganas et al 1998;Neubauer et al, 1998). Our preliminary experiments, however, indicated that none of the transgenes used in this study (ras12V, ras17N, and MAPKKm) induced signi®cant alterations in the basal or EPO-induced phosphorylation of endogenous Jak2 protein nor did the ras17N gene a ect the DNAbinding activity of endogenous STAT5 protein (our unpublished observation).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…There is also good evidence suggesting essential role for Jak2-STAT5 pathway in erythropoiesis in vitro and in vivo (Wakao et al, 1997;Iwatsuki et al, 1997;Parganas et al 1998;Neubauer et al, 1998). Our preliminary experiments, however, indicated that none of the transgenes used in this study (ras12V, ras17N, and MAPKKm) induced signi®cant alterations in the basal or EPO-induced phosphorylation of endogenous Jak2 protein nor did the ras17N gene a ect the DNAbinding activity of endogenous STAT5 protein (our unpublished observation).…”
Section: Discussionmentioning
confidence: 58%
“…Conversely, forced expression of protein tyrosine phosphatase b2 gene was found to induce di erentiation in murine erythroleukemia cells (Kume et al, 1996). In addition, Jak2-de®cient mice were found to have defects in de®nitive erythropoiesis which lead to embryonic death due to anemia (Parganas et al, 1998;Neubauer et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…JAK-2 mediates signaling via the hematopoietic cytokines EPO, GM-CSF, and thrombopoietin (8,9). Patients receiving the highest dosage of CP-690,550 (30 mg twice daily) had higher incidences of anemia, granulocytopenia, and thrombocytopenia than did the placebo group (12).…”
Section: Discussionmentioning
confidence: 99%
“…Tyk-2 deficiency results in a human primary immunodeficiency similar to the JAK-3 SCID phenotype; however, neither JAK-1-deficient nor JAK-2-deficient humans have been identified, and deficient mice are not viable (8,9). Several of the cytokines that require JAK-1, JAK-2, and/or Tyk-2 activity, including IL-6, IL-12, and IL-23, play a pathogenic role in human rheumatoid arthritis (RA) (10,11), suggesting that inhibiting the JAK family more broadly may be beneficial.…”
mentioning
confidence: 99%
“…Gene targeting studies in mice have illustrated the importance of the Jak family members in hematopoiesis. Lymphoid development is impaired in mice deficient in Jak1 (Rodig et al, 1998) and Jak3 (Nosaka et al, 1995;Park et al, 1995;Thomis et al, 1995), and erythropoiesis is lost in Jak2-deficient mice (Parganas et al, 1998). Loss of Jak3 has also been implicated in dysregulated myelopoiesis (Grossman et al, 1999).…”
Section: Introductionmentioning
confidence: 99%